Analisis Keandalan Mesin Produksi Tissue Basah - Sulistyarini, Dwi Hadi; Setyarini, Putu Hadi; Cahyawati, Amanda Nur (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2019)
The wet tissue company in this research has 46 volpack machines, 44 are used to produce wet sanitizer tissue and 2 other machines are used to produce wet cologne tissue. During this time, the company produces cologne type wet tissue where its production does not reach the production target. One of the causes of this problem was the high downtime influenced by the reliability of these components and machine; so causing the production capacity of wet cologne tissue to be reduced and company's production targets not achieved. Therefore, in order to achieve the company's production targets and to make the production process more efficient and effective, it is necessary good maintenance actions that pay attention to the reliability value of each critical component. This study analyzes the reliability of critical components so that companies can take action to increase their machine reliability.